2009
DOI: 10.1007/s12204-009-0398-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the effect of cyclic preloading on the resistance to liquefaction of saturated loose sand under wave loading

Abstract: By using the soil static and dynamic universal triaxial and torsional shear apparatus, a series of combined cyclic shear tests are performed to simulate the rotation in the principal stress direction induced by ocean wave. The tests include the cyclic preloading tests and liquefaction tests in the second loading on saturated loose sand with a relative density of 30%. The all tests are consolidated under isotropic condition. The effect of the cyclic preloading on the resistance to liquefaction of saturated loos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…To a greater extent, it is attributed to the formation of a more stable structure of soil particles during the small vibration in Test A. The experimental results of the triaxial and torsional shear tests conducted by Zhang et al (2009) andWichtmann et al (2005) also showed that the cyclic preloading of small amplitudes causes a negligible reduction in the void ratio, but improves significantly the liquefaction resistance of sand. These results were attributed to the fabric change of soil resulting from the uniformity of the void ratio and better interlocking of particles during cyclic preloading.…”
Section: Effect Of Shaking Historymentioning
confidence: 92%
See 1 more Smart Citation
“…To a greater extent, it is attributed to the formation of a more stable structure of soil particles during the small vibration in Test A. The experimental results of the triaxial and torsional shear tests conducted by Zhang et al (2009) andWichtmann et al (2005) also showed that the cyclic preloading of small amplitudes causes a negligible reduction in the void ratio, but improves significantly the liquefaction resistance of sand. These results were attributed to the fabric change of soil resulting from the uniformity of the void ratio and better interlocking of particles during cyclic preloading.…”
Section: Effect Of Shaking Historymentioning
confidence: 92%
“…However, as pointed out by Finn et al (1970), preshearing influences the liquefaction resistance of saturated sand according to triaxial and simple shear cyclic loading tests. The experimental studies by Zhang et al (2009) and Wichtmann et al (2005) also indicated that the cyclic preloading could improve the liquefaction resistance of sand under the condition that liquefaction does not occur during the cyclic preloading. Therefore, the effect of shaking history on seismic ground response cannot be ignored.…”
Section: Introductionmentioning
confidence: 95%